2017
DOI: 10.5194/gmd-10-1261-2017
|View full text |Cite
|
Sign up to set email alerts
|

Global methane emission estimates for 2000–2012 from CarbonTracker Europe-CH<sub>4</sub> v1.0

Abstract: Abstract. We present a global distribution of surface methane (CH4) emission estimates for 2000–2012 derived using the CarbonTracker Europe-CH4 (CTE-CH4) data assimilation system. In CTE-CH4, anthropogenic and biospheric CH4 emissions are simultaneously estimated based on constraints of global atmospheric in situ CH4 observations. The system was configured to either estimate only anthropogenic or biospheric sources per region, or to estimate both categories simultaneously. The latter increased the number of op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(116 citation statements)
references
References 104 publications
5
107
3
1
Order By: Relevance
“…CTDAS is used at the Finnish Meteorological Institute (FMI) for the development of CarbonTracker Europe Methane (CTE-CH 4 ) and is used to perform global methane inversions (Tsuruta et al, 2015(Tsuruta et al, , 2017 CTDAS has also been used for the optimization of transport properties of the underlying TM5 model using observations of SF 6 (van der Veen, 2013). Previous studies demonstrated that many models, including TM5, poorly simulate the SF 6 gradients between the Northern Hemisphere (NH) and Southern Hemisphere (SH), which is mainly controlled by transport across the intertropical convergence zone (ITCZ).…”
Section: Overview Of Applications Using Ctdasmentioning
confidence: 99%
“…CTDAS is used at the Finnish Meteorological Institute (FMI) for the development of CarbonTracker Europe Methane (CTE-CH 4 ) and is used to perform global methane inversions (Tsuruta et al, 2015(Tsuruta et al, , 2017 CTDAS has also been used for the optimization of transport properties of the underlying TM5 model using observations of SF 6 (van der Veen, 2013). Previous studies demonstrated that many models, including TM5, poorly simulate the SF 6 gradients between the Northern Hemisphere (NH) and Southern Hemisphere (SH), which is mainly controlled by transport across the intertropical convergence zone (ITCZ).…”
Section: Overview Of Applications Using Ctdasmentioning
confidence: 99%
“…All these flux terms respond to changes in local temperature, precipitation, nutrient availability, and other key environmental variables (Friedlingstein et al, 2006). Extreme climate events such as droughts can decrease GPP and increase TER and fire disturbances to a point where regional NEE is turned into a temporary carbon source (Ciais et al, 2005;Gatti et al, 2014;van der Laan-Luijkx et al, 2015). These dynamic responses (and positive feedbacks whereby increased CO 2 may lead to more droughts) are now an integral part of climate models that include fully coupled carbon cycling (Booth et al, 2012;Dai , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In so-called double-deconvolution methods this particular trait is used to untangle the global land carbon budget from the ocean carbon budget (Keeling et al, 1989;Tans et al, 1993;Ciais et al, 1995). More recently, the 13 C isotope was used to study the diurnal cycle of GPP and TER (Wehr et al, 2016) and was used as a tracer of water use efficiency to study long-term responses to CO 2 increases in tree rings (van der Sleen et al, 2015), and attempts are underway to do the same based on atmospheric records. On regional scales, variations in the ratio of 13 CO 2 / 12 CO 2 (typically reported as δ 13 C in ‰ relative to the VPDB reference ratio) reflect changes in discrimination processes associated with photosynthetic uptake of carbon by plants (e.g., Farquhar et al, 1989;Fung et al, 1997;Scholze et al, 2003;Rayner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations